Analisis Perspektif Guru Terhadap Chat GPT di SMK Negeri 1 Bangli - I Putu Rama Putra Yasa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine teachers' perspectives on ChatGPT at SMK Negeri 1 Bangli. This study wants to determine the effectiveness of ChatGPT in helping students understand lesson concepts, ease of access to information, and its impact on student motivation and engagement in learning. In addition, this study also wants to explore teachers' concerns related to the use of ChatGPT, such as the potential for students' dependence on technology and the occurrence of delays in students in various aspects. This study uses a descriptive qualitative approach with a data collection method through interviews with 9 teachers at SMK Negeri 1 Bangli. The results show that the majority of teachers are aware of the potential of ChatGPT in increasing students' motivation to learn, but are also worried about students' dependence on this technology. The study concluded that ChatGPT has the potential to improve the quality of education, but it needs to be used responsibly to avoid the negative impact it can have. Teachers need to understand the potential and drawbacks of ChatGPT to teach students how to use it responsibly. Schools need to create clear policies about the use of ChatGPT in learning. ChatGPT developers need to continue to improve the accuracy and relevance of the information generated by ChatGPT.